2021
DOI: 10.3389/fnins.2021.776809
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenome in Neurodevelopmental Disorders

Abstract: Neurodevelopmental diseases (NDDs), such as autism spectrum disorders, epilepsy, and schizophrenia, are characterized by diverse facets of neurological and psychiatric symptoms, differing in etiology, onset and severity. Such symptoms include mental delay, cognitive and language impairments, or restrictions to adaptive and social behavior. Nevertheless, all have in common that critical milestones of brain development are disrupted, leading to functional deficits of the central nervous system and clinical manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 302 publications
(455 reference statements)
2
20
0
Order By: Relevance
“…Importantly, various molecules involved in the regulation of gene expression have been implicated in the emergence of MCD. Transcription factors, notably PAX6, TBR2, EMX2, FOXG1, ARX, DMRTA2, and others ( Mallamaci et al, 2000 ; Kitamura et al, 2002 ; Ligon et al, 2003 ; Baala et al, 2007 ; Asami et al, 2011 ; Baek et al, 2015 ; Urquhart et al, 2016 ), as well as epigenetic mechanisms, including histone modifications, chromatin remodeling and RNA-level regulation, have been shown to play an important role in the onset of MCDs ( Qiao et al, 2016 ; Silver, 2016 ; Albert and Huttner, 2018 ; Doan et al, 2018 ; Gabriele et al, 2018 ; Franz et al, 2019 ; Ciptasari and van Bokhoven, 2020 ; Vaid and Huttner, 2020 ; Reichard and Zimmer-Bensch, 2021 ; Wilson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, various molecules involved in the regulation of gene expression have been implicated in the emergence of MCD. Transcription factors, notably PAX6, TBR2, EMX2, FOXG1, ARX, DMRTA2, and others ( Mallamaci et al, 2000 ; Kitamura et al, 2002 ; Ligon et al, 2003 ; Baala et al, 2007 ; Asami et al, 2011 ; Baek et al, 2015 ; Urquhart et al, 2016 ), as well as epigenetic mechanisms, including histone modifications, chromatin remodeling and RNA-level regulation, have been shown to play an important role in the onset of MCDs ( Qiao et al, 2016 ; Silver, 2016 ; Albert and Huttner, 2018 ; Doan et al, 2018 ; Gabriele et al, 2018 ; Franz et al, 2019 ; Ciptasari and van Bokhoven, 2020 ; Vaid and Huttner, 2020 ; Reichard and Zimmer-Bensch, 2021 ; Wilson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic mechanisms are fundamental for the development and function of the central nervous system, and their impairment contributes to neurodevelopmental (Reichard and Zimmer-Bensch, 2021), neuromuscular (Coppedè, 2020), and neurodegenerative disorders (Gagliardi et al, 2018;Bellver-Sanchis et al, 2021). As such, active research is ongoing to identify epigenetic biomarkers of these disorders, and both DNA methylation changes and circulating RNAs are increasingly recognized as potential biomarkers to improve diagnosis and to monitor disease status and response to therapeutic interventions (Sproviero et al, 2021;Hirunagi et al, 2022;Kaur et al, 2022).…”
Section: Epigenetics Of Neurodevelopmental Neuromuscular and Neurodeg...mentioning
confidence: 99%
“…Histone modifications, such as acetylation, phosphorylation, methylation, ubiquitination, and sumoylation, play a significant role in the regulation of the chromatin structure 75 . Evidence gained from the study of neurodevelopmental defects indicates that histone modification is essential for normal neural development 76,77 . Several studies have confirmed that specific histone modifications correlate with the onset of NTDs in embryos 27,78–80 .…”
Section: Histone Modifications Related To Ntds In the Human Neural Ti...mentioning
confidence: 99%